Factors associated with time from first-symptoms to diagnosis and treatment initiation of Multiple Sclerosis in Switzerland. Issue 4 (December 2018) - Kaufmann, Marco; Kuhle, Jens; Puhan, Milo A; Kamm, Christian P; Chan, Andrew; Salmen, Anke; Kesselring, Jürg; Calabrese, Pasquale; Gobbi, Claudio; Pot, Caroline; Steinemann, Nina; Rodgers, Stephanie; et al.
Background: Recent studies emphasise the importance of timely diagnosis and early initiation of disease-modifying treatment in the long-term prognosis of multiple sclerosis. Objectives: The objective of this study was to investigate factors associated with extended time to diagnosis and time to disease-modifying treatment initiation in the Swiss Multiple Sclerosis Registry. Methods: We used retrospective data (diagnoses 1996–2017) of the survey-based Swiss Multiple Sclerosis Registry and fitted logistic regression models (extended time to diagnosis ≥2 years from first symptoms, extended time to disease-modifying treatment initiation ≥1 year from diagnosis) with demographic and a priori defined variables. Results: Our study, based on 996 persons with multiple sclerosis, suggests that 40% had an extended time to diagnosis, and extended time to disease-modifying treatment initiation was seen in 23%. Factors associated with extended time to diagnosis were primary progressive multiple sclerosis (odds ratio (OR) 5.09 (3.12–8.49)), diagnosis setting outside of hospital (neurologist (private practice) OR 1.54 (1.16–2.05)) and more uncommon first symptoms (per additional symptom OR 1.17 (1.06–1.30)). Older age at onset (per additional 5 years OR 0.84 (0.78–0.90)) and gait problems (OR 0.65 (0.47–0.89)) or paresthesia (OR 0.72 (0.54–0.95)) as first symptoms were associated with shorter time to diagnosis. Extended time to disease-modifying treatment initiation was associated with older age at diagnosis (per additional 5 years OR 1.18 (1.09–1.29)). In more recent years, time to diagnosis and time to disease-modifying treatment initiation tended to be shorter. Conclusions: Even in recent periods, substantial and partially systematic variation regarding time to diagnosis and time to disease-modifying treatment initiation remains. With the emerging paradigm of early treatment, the residual variation should be monitored carefully.